Killing the cat? A review of curiosity at work - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2022)
This paper focuses on the emergent importance of curiosity at work for individuals and organizations by reviewing management research on curiosity at work. We start by leveraging prior reviews on early and contemporary foundations of the curiosity construct in the larger psychological literature, with a focus on definitional clarity, dimensionality, and differences with other constructs in its nomological network. Next, we review different streams of management research on curiosity at work (i.e., broad generative and nongenerative effects, curiosity as a catalyst for personal action, curiosity as a catalyst for interpersonal action, curiosity as a catalyst for leadership, curiosity as an organizational or professional norm, and curiosity as a catalyst for organizing). Interweaving these diverse literatures and research streams gives us the wherewithal to provide conceptual clarity in curiosity research and highlight how curiosity has not only generative effects at the individual level but acts also as a more dynamic, interpersonal, and organizational property. In addition, our review brings attention to the potential dark side of curiosity. We end by outlining how the more nuanced insights of the role of curiosity at work generated by our review provide an impetus for future research.